Evaluation of community pharmacists' professional practice and management of patient's respiratory conditions - Raja'a A Al-Qudah; Rana Abu-Farha; Maram M Al-Ali; Nour S Jaradaneh; Mohamed Izham Mohamed Ibrahim (Wolters Kluwer Medknow Publications, 2021)
Objectives: We assessed the extent of community pharmacists managing respiratory conditions and their ability to make differential diagnoses between the common cold and allergic rhinitis. Methods: A simulated patient technique was used to achieve the study objectives. Thirty community pharmacies were randomized to be visited by a patient with allergic rhinitis symptoms, followed by a patient with common cold symptoms, and vice versa. One simulated patient visited the 15 pharmacies assigned to allergic rhinitis. Then, after 3-4 days, the pharmacies were revisited by a second simulated patient using the same symptoms; likewise, a simulated patient visited the other 15 pharmacies with common cold symptoms. Then, these pharmacies were revisited by the other simulated patient with the common cold symptoms. Descriptive statistics and correlation analyses were carried out using SPSS at alpha 0.05. Results: Fifteen pharmacies were used for the common cold scenario and 15 for the allergic rhinitis scenario (a total of 30 visits per scenario). Pharmacists showed overall poor skills in asking questions for differential diagnosis between the two conditions. No significant difference was found in the overall differential diagnosis score between the two groups (P = 0.744). The overall adherence to the labeling standard score was low, with an average of 2.38 (standard deviation [SD] = 2.50) out of 11, with no significant difference between the two scenarios (P = 0.332). The overall adherence score to the counseling standard was low, with an average of 2.93 (SD = 3.74) out of 15, with no significant difference between the two scenarios (P = 0.586). Conclusion: The simulated patient technique approach revealed a lack of ability of pharmacists in Amman, Jordan, to make differential diagnoses between the common cold and allergic rhinitis. In addition, pharmacists lacked the ability to carry out their role with respect to the management of the common cold and allergic rhinitis, including treatment recommendations, adherence to medicine labeling standards, and adherence to the counseling standard.